Advances and Prospects of Sulfide All‐Solid‐State Lithium Batteries via One‐to‐One Comparison with Conventional Liquid Lithium Ion Batteries. Issue 29 (29th May 2019) - Lee, Hyomyung; Oh, Pilgun; Kim, Junhyeok; Cha, Hyungyeon; Chae, Sujong; Lee, Sanghan; Cho, Jaephil
Abstract: Owing to the safety issue of lithium ion batteries (LIBs) under the harsh operating conditions of electric vehicles and mobile devices, all‐solid‐state lithium batteries (ASSLBs) that utilize inorganic solid electrolytes are regarded as a secure next‐generation battery system. Significant efforts are devoted to developing each component of ASSLBs, such as the solid electrolyte and the active materials, which have led to considerable improvements in their electrochemical properties. Among the various solid electrolytes such as sulfide, polymer, and oxide, the sulfide solid electrolyte is considered as the most promising candidate for commercialization because of its high lithium ion conductivity and mechanical properties. However, the disparity in energy and power density between the current sulfide ASSLBs and conventional LIBs is still wide, owing to a lack of understanding of the battery electrode system. Representative developments of ASSLBs in terms of the sulfide solid electrolyte, active materials, and electrode engineering are presented with emphasis on the current status of their electrochemical performances, compared to those of LIBs. As a rational method to realizing high energy sulfide ASSLBs, the requirements for the sulfide solid electrolytes and active materials are provided along through simple experimental demonstrations. Potential future research directions in the development of commercially viable sulfide ASSLBs are suggested. Abstract : Recent progress on sulfide all‐solid‐state lithium batteries (ASSLBs) and their battery performance with respect to materials, electrodes, and cell design are reviewed. Furthermore, by one‐to‐one comparison with conventional lithium‐ion battery (LIB) technologies, the current status of ASSLB development is explained and the future research direction is determined.